Clinical and laboratory data of primary hemophagocytic lymphohistiocytosis: A retrospective review of the Turkish Histiocyte Study Group - (:unkn) unknown (GALENOS YAYINCILIK, 2010)
Objective: This study analyzes the clinical and laboratory findings of children with primary hemophagocytic lymphohistiocytosis (HLH) followed in various referral centers of Turkey. Materials and Methods: A simple three-page questionnaire prepared by the Turkish Histiocyte Study Group was used for documentation of patient data. Results: Age at diagnosis varied from 0.6 to 78 months (median +/- SD, 16.5 +/- 26.1). Sex distribution was almost equal (F/M= 10/12). The frequencies of parental consanguinity and sibling death in the family history were 100% and 81.1%, respectively. The most common clinical findings were hepatomegaly (100%) and fever (95%). The most common laboratory findings were anemia (100%), hyperferritinemia (100%) and thrombocytopenia (90.9%). Triglyceride and total bilirubin levels in the deceased versus surviving group appear to be high (triglyceride: 394 +/- 183 mg/dl, 289 +/- 7 mg/dl; total bilirubin: 2.7 +/- 6.9 mg/dl, 0.5 +/- 1.2 mg/dl, respectively). Conclusion: We concluded that fever, hepatosplenomegaly, anemia, thrombocytopenia, and hyperferritinemia are the most common clinical and laboratory findings in primary HLH. Increased triglyceride and total bilirubin level at the time of diagnosis might be an indicator of poor prognosis in HLH. (Turk J Hematol 2010; 27: 157-62)
Keywords: Primary hemophagocytic lymphohistiocytosis; clinical and laboratory findings; SYNTAXIN-11; MUTATIONS; DIAGNOSIS; CHILDREN